Aaqueous exposure to silver nanoparticles synthesized by abalone viscera hydrolysates promotes the growth, immunity and gut health of zebrafish (Danio rerio) - Ni, Jing; Yang, Zhuan; Zhang, Yue; Ma, Ying; Xiong, Hejian; Jian, Wenjie (Frontiers in Microbiology, 2022)
Silver nanoparticles (AgNPs) have the potential to be used in aquaculture, but their influence on the growth and health of aquatic organisms has not been extensively investigated. In this study, the abalone viscera hydrolysates decorated AgNPs (AVH-AgNPs) were dispersed into aquaculture water at different concentrations (0, 6, 9, and 18 μg/L) to evaluate the biological effects on zebrafish (Danio rerio). The results showed that the AVH-AgNPs treatments of 6 and 9 μg/L promoted the growth and did not cause obvious damage to the gills, intestines, and livers of zebrafish. All the treatments induced catalase (CAT) and superoxide dismutase (SOD) activities and increased glutathione (GSH) content in the livers and upregulated the expression of immune related genes. The effects of 9 and 18 μg/L AVH-AgNPs treatments were more obvious. After AVH-AgNPs treatment, the abundances of some potential pathogens, such as species Plesimonas shigelloides and Pseudomonas alcaligenes and genus Flavobacterium decreased significantly. In contrast, the abundance of some beneficial bacteria that can degrade pollutants and toxins (e.g., Rhodococcus erythropolis) increased significantly. Thus, the application of low concentrations (6～18 µg/L) of AVH-AgNPs in aquaculture water is relatively safe and has a positive effect on zebrafish farming.